ANALYSIS OF WATER QUALITY ON THE PRODUCTIVITY OF SEAWEED CULTIVATION OF Kappaphycus alvarezii IN WEST SEBATIK DISTRICT, NUNUKAN REGENCY - Novita Trisnawati Tarzanto; Indra Cahyono (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2026)
Water quality is a critical factor influencing the growth and productivity of seaweed cultivation. This study aimed to analyze the relationship between water quality characteristics and the productivity of Kappaphycus alvarezii cultivated using the long-line method in West Sebatik District, Nunukan Regency. The study was conducted from September to December 2025 in three villages, namely Setabu, Binalawan, and Liang Bunyu, using a quantitative approach with an observational and descriptive-analytical design. Water quality parameters measured included temperature, salinity, pH, dissolved oxygen, transparency, current velocity, depth, nitrate, and phosphate. Productivity was evaluated based on growth performance and annual production. The results indicated that all water quality parameters were generally within suitable ranges for seaweed cultivation. Binalawan exhibited the highest transparency (1.50 ± 0.15 m) and phosphate concentration (0.30 ± 0.06 mg L⁻¹), resulting in the highest biomass (388 g) and specific growth rate (4.182% day⁻¹). Liang Bunyu recorded the highest annual dry production (6,435 tons year⁻¹) due to its larger cultivation area. The findings highlight the importance of water quality management and site selection in improving the productivity and sustainability of K. alvarezii cultivation